Xylan-Based Hydrogels as a Potential Carrier for Drug Delivery: Effect of Pore-Forming Agents - Minmin Chang; Xinxin Liu; Ling Meng; Xiaohui Wang; Junli Ren (MDPI AG, 2018)
Pore-forming agents have a significant influence on the pore structure of hydrogels. In this study, a porogenic technique was employed to investigate the preparation of macroporous hydrogels which were synthesized by radical copolymerization of carboxymethyl xylan with acrylamide and N-isopropylacrylamide under the function of a cross-linking agent. Six kinds of pore-forming agents were used: polyvinylpyrrolidone K30, polyethylene glycol 2000, carbamide, NaCl, CaCO3, and NaHCO3. The application of these hydrogels is also discussed. The results show that pore-forming agents had an important impact on the pore structure of the hydrogels and consequently affected properties of the hydrogels such as swelling ratio and mechanical strength, while little effect was noted on the thermal property of the hydrogels. 5-Fluorouracil was used as a model drug to study the drug release of the as-prepared hydrogels, and it was found that the drug release was substantially improved after using the NaHCO3 pore-forming agent: a cumulative release rate of up to 71.05% was achieved.